(х+1)(х во второй степени - х+1)-х(х+2)(х-2)=3 Х в третьей степени - 8- 2х=(х-2)

0 голосов
50 просмотров

(х+1)(х во второй степени - х+1)-х(х+2)(х-2)=3 Х в третьей степени - 8- 2х=(х-2)


Алгебра (23 баллов) | 50 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

(х+1)(х²-х+1)-х(х+2)(х-2)=3

х³+х²-х²-х+х+1-х(х²-4)=3

х³+1-х³+4х=3

4х+1=3

4х=2

х=1/2

Отвтет: х=1/2

 

Проверка:

(1/2+1)(1/4-1/2+1)-1/2*(1/2+2)(1/2-2) = (3/2)*(3/4)-1/2*(5/2)*(-3/2) = (9/8)+15/8 = 124/8 = 3 - верно.

 

х³-8-2х=(х-2)

х³-8-2х-х+2=0

х³-6-х=0

x=2.

 

Ответ: х=2

(4.2k баллов)
0 голосов

фывапролджэждлорпавывапролдж


image
(818 баллов)